Penerapan Model Problem Based Learning Untuk Meningkatkan Keterampilan Proses dan Hasil Belajar IPA pada Siswa Kelas V SDN Ngampel Tahun Ajaran 2022/2023 - Oktaviyanti, Melli; Ngatman, Ngatman; Suryandari, Kartika Chrysti (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2023)
The study aimed to improve process skills and natural science learning outcomes about heat transfer to fifth grade students through the implementation of Problem Based Learning. This class action research was conducted in three cycles. The subjects were teachers and students of fifth grade at SD Negeri Ngampel. The data were qualitative and quantitative. Data collection techniques were observation, interviews, and tests. Data validity used triangulation of source and triangulation of techniques. Data analysis included data reduction, data presentation, and drawing conclusions. Problem Based Learning improved the process skills and natural science learning outcomes. The percentages of process skills were 66.67% in the first cycle, 78.33% in the second cycle, and 86.67% in the third cycle. The passing grades on students' cognitive learning outcomes were 66.67% in the first cycle, 80.95% in the second cycle, and 90.47% in the third cycle. On the students’ scientific attitude, the average percentages were 66.67% in the first cycle, 77.78% in the second cycle, and 86.11% in the third cycle. It concludes that Problem Based Learning improves process skills and natural science learning outcomes to fifth grade students of SDN Ngampel in academic year of 2022/2023